2022
DOI: 10.1002/ppul.26110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of camel milk in asthmatic children: A double‐blind randomized pilot study

Abstract: Objective Asthma is one of the prevalent diseases in children. There is some evidence regarding the benefits of camel milk in asthma. The present study was carried out to evaluate the effect of camel milk on asthmatic children. Patients and Methods A randomized double‐blind pilot study was operated in 2018 in a tertiary center. Sixty children aged more than 6 years with not well‐controlled asthma were included. The intervention was consisting of 200‐ml camel milk or placebo daily for 2 months. The medication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This effect has been noted in humans, rats [79,80], and alloxan-induced diabetic dogs [81]. Furthermore, several studies have demonstrated the potential therapeutic effects of camel milk in treating rheumatoid arthritis and asthma [82,83]. These findings suggest that camel milk consumption may elicit anti-inflammatory actions and could be used as an adjunctive therapeutic approach for managing these conditions.…”
Section: Therapeutic Applications Of Camel Milkmentioning
confidence: 80%
“…This effect has been noted in humans, rats [79,80], and alloxan-induced diabetic dogs [81]. Furthermore, several studies have demonstrated the potential therapeutic effects of camel milk in treating rheumatoid arthritis and asthma [82,83]. These findings suggest that camel milk consumption may elicit anti-inflammatory actions and could be used as an adjunctive therapeutic approach for managing these conditions.…”
Section: Therapeutic Applications Of Camel Milkmentioning
confidence: 80%
“…Patients ( n = 30) were provided 200 mL of camel's milk to drink daily for 2 months, and 30 patients were provided cow's milk as a placebo. There was a statistically significant improvement in the reported symptoms and a decrease in the use of short‐acting beta agonists in the study group 15 . This improvement was postulated to be secondary to higher content of immunoglobulin G (IgG) and anti‐inflammatory properties in camel's milk.…”
Section: Updates In Biologic Treatments and Alternative Interventions...mentioning
confidence: 92%
“…There was a statistically significant improvement in the reported symptoms and a decrease in the use of short-acting beta agonists in the study group. 15 This improvement was postulated to be secondary to higher content of immunoglobulin G (IgG) and anti-inflammatory properties in camel's milk. Of note, there were no significant differences in spirometry values between the two groups.…”
Section: Updates In Biologic Treatments and Alternative Interventions...mentioning
confidence: 99%